HALAL PRODUCT ASSURANCE SYSTEM FOR “KING CRYSTAL ICE” BUSINESS OWNERS IN LHOKSEUMAWE CITY, ACEH PROVINCE: SOSIALISASI SISTEM JAMINAN PRODUK HALAL BAGI PELAKU USAHA ES KRISTAL ”KING ICE” DI KOTA LHOKSEUMAWE PROVINSI ACEH - Cut Nelly; Ika Rezvani Aprita; Saudah; Marlina; Chairil Anwar; Suri Purnama Febri; Suraiya Nazlia; Kurnia (WISDOM : Jurnal Pengabdian Kepada Masyarakat Wisdom, 2025)
"King Ice" is a crystal ice production business in Lhokseumawe. This business supplies crystal ice to small and medium-sized businesses in the city. The owner of "King Ice" is still unaware of the benefits and objectives of the halal certification process.  The considers the halal certification process complicated due to the lack of information. This community service activity is a collaboration between lecturers and students from various universities. It consists of preparation and implementation stages to socialize the halal product assurance system. The results of the community service activity demonstrate the interest and willingness of the owner of "King Ice" to participate in the halal certification process to increase consumer trust and product quality.